Farm and factory : an analysis of the distinctions between and fiscal treatment of taxpayers simultaneously carrying on farming operations and manyfacturing processes under the Income Tax Act No. 58 of 1962 - Katzke, August Charles Rudolf (Department of Commercial Law, 2015)
Includes abstract.